2000
DOI: 10.1002/1097-0061(20000630)16:9<829::aid-yea581>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptional autoregulatory loop for KIN28–CCL1 and SRB10–SRB11, each encoding RNA polymerase II CTD kinase–cyclin pair, stimulates the meiotic development of S. cerevisiae

Abstract: Alkalization of the medium is associated with and required for the cellular development to meiosis and sporulation in the yeast Saccharomyces cerevisiae. To elucidate the molecular mechanisms for the signi®cance of external alkalization, we isolated mutants defective in division arrest at G 1 phase under an alkaline condition. The mutants obtained had recessive alleles of SRB10 encoding the cyclin (SRB11)-dependent protein kinase that phosphorylates the CTD domain of the largest subunit of RNA polymerase II an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…We next asked whether the effects of SUB1 deletion on Srb10 might contribute to the effects we observed on Kin28. Previous studies have shown that TFIIH is negatively regulated by CDK8-containing Mediator complexes in human cells (4) and that Srb10 inhibits KIN28 transcription in meiotic yeast cells (51). Extending these results, we observed that deletion of SRB10 resulted in an increase in Kin28-HA levels and, as a consequence, an increase in Kin28 activity, as analyzed by in vitro kinase assays (Fig.…”
Section: (D)supporting
confidence: 83%
“…We next asked whether the effects of SUB1 deletion on Srb10 might contribute to the effects we observed on Kin28. Previous studies have shown that TFIIH is negatively regulated by CDK8-containing Mediator complexes in human cells (4) and that Srb10 inhibits KIN28 transcription in meiotic yeast cells (51). Extending these results, we observed that deletion of SRB10 resulted in an increase in Kin28-HA levels and, as a consequence, an increase in Kin28 activity, as analyzed by in vitro kinase assays (Fig.…”
Section: (D)supporting
confidence: 83%
“…The KRH1 gene was identified previously by a mutation that causes cells to continue to grow when incubated in alkaline sporulation medium (Ohkuni and Yamashita, 2000). This medium contains acetate as a carbon source and is limiting for nitrogen, a nutritional condition that induces sporulation in wild-type cells.…”
Section: Discussionmentioning
confidence: 99%
“…Respiration leads to the production of CO2 and hence causes alkalization of the medium. This alkalization may contribute to meiotic initiation (Ohkuni and Yamashita, 2000). For example Rim101p is required both for adaptation to extracellular alkalization ) and for IME1 transcription (Su and Mitchell, 1993).…”
Section: Nitrogen Starvationmentioning
confidence: 99%
“…For example Rim101p is required both for adaptation to extracellular alkalization ) and for IME1 transcription (Su and Mitchell, 1993). In addition, alkalization of the medium may also activate the Srb10p-Srb11p cyclinkinase complex (also called Ume3p-Ume5p and Ssn3p-Ssn8p), and this activation is required for efficient induction of IME2 transcription and initiation of meiosis (Cooper and Strich, 2002;Ohkuni and Yamashita, 2000). Thus respiration may promote both IME1 and IME2 expression by causing alkalization of the medium.…”
Section: Nitrogen Starvationmentioning
confidence: 99%